A scenario analysis of once-through thorium fuel cycles with pressure tube HWRs in Canada. (January 2018) - Wojtaszek, D.; Colton, A.V.; Bromley, B.P.; Edwards, G.W.R.; Levinsky, A.
Highlights: SEU + Thorium fuel in PT-HWRs has a number of benefits to the fuel cycle. Reduced resource consumption by 23% relative to NU fuel. Reduced number of DGR used fuel containers by up to 60% Reduced number of dry storage baskets by up to 32% Abstract: Thorium-based fuel cycles offer many potential benefits, including greater long-term energy sustainability and improved waste management, relative to uranium-based fuels. The purpose of this study was to analyze the potential impacts associated with deploying thorium-based fuels in Pressure Tube Heavy Water Reactors (PT-HWRs) in a once-through fuel cycle in Canada, and to compare them with the use of conventional Natural Uranium (NU) fuel. This study analyzed a medium-burnup (∼19.1 MWd/kg) Slightly Enriched Uranium-based fuel augmented by small amounts of thorium (SEU + Th) and a high-burnup (∼40.6 MWd/kg) fuel made with Low Enriched Uranium mixed with thorium (LEU/Th). The deployment of the medium-burnup SEU + Th in Canada reduced resource consumption by 23% relative to the low burnup NU fuel. The medium-burnup fuel required 3% to 60% fewer Deep Geological Repository (DGR) Used Fuel Containers (UFCs) relative to the low burnup fuel, depending on the decay time (10–70 years) of the Used Nuclear Fuel (UNF). Extending the decay duration of UNF decreases its decay power per unit mass, and hence the required number of DGR UFCs per mass of UNF, at the expense of requiring more above-ground dry storage capacity.